Drafting of 2 swimmers in open-water - Bolon, B.; Pretot, C.; Larrarte, F.; Clanet, C.; Carmigniani, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The word drafting defines the benefit obtained by an athlete from the wake of an opponent. Drafting is observed in various sports such as team sports or when racing against other athletes: running, swimming, car racing or cycling. The main idea is that an athlete can benefit from a drag reduction when being behind another one. Therefore, the draft athlete produces less effort than their opponent to move at the same speed. This energy saving can make a difference in the outcome of a race. In swimming, athletes move at the interface between air and water, which makes drafting in swimming specific because of the waves created at this interface. Different studies have monitored physiological parameters and their evolution in drafting configurations [1, 2, 3]. These articles draw the conclusion that drafting has a positive impact on physiological parameters such has a reduction of the concentration of blood lactate, a reduction in oxygen uptake and heart rate and a reduced perceived exertion on the Borg scale. As a consequence, draft swimmers will face less physical fatigue than isolated swimmers. Moreover, Janssen et al. [3] also shown a positive correlation between passive drag reductions in drafting formation and physiological benefit in active swimming in those same formations. There are also numerical papers that study drag forces and drag coefficients on passive swimmers [4, 5]. They suggest that the drafted swimmer encounters reduced drag compared to the leading swimmer, which can explain the evolution of physiological parameters mentioned before. The wave field created by a passive leading swimmer has been studied by Yuan et al. [6], using a potential theory approach and neglecting the wake produced by the swimmers. They found that a draft swimmer following a leader could encounter a drag increase or decrease depending on the distance separating the 2 swimmers. Finally, some works try to actually measure drag during drafting experimentally. For example, Westerweel [7] did some drag measurements on scale models and concluded that the drag reduction could be up to 40% for the draft swimmer. Our goal is to determine the relative positions of swimmers that allow them to make the most of drafting during open-water races. The study is conducted on passive scale models, which allows us to study a wide range of race configurations.